Pengaruh Peregangan – Pemanasan dan Pemanasan – Peregangan Terhadap Kecepatan Lari 54,86 Meter (60 Yard) - Sulikan Sulikan (IKIP Budi Utomo Malang, 2018)
The purpose of the the research is to know the effectiveness of the inﬂuence of stretching-up and warming-up-stretching toward the velocity of 60 yard dash. Population used are the students ( male ) of IKIP Budi Utomo Malang S1 program especially the ffth semester. Here the writer takes 80 students as samples from 178 students ramdomly. The samples are divided into 4 gruops by matching them that each group consists of 20 students.The kind of research experiments is using the design of the study latin square. The experiments is done about 4 weeks, once a week. That uses four treatmen as follow : treatment A, B, C and D. Each group is treated differently a week, so in 4 weeks all group will have same 4 kind of treatment. Tehnik collecting data obtained from pre-test and post-test that carried on four times.The analysis of data obtained Anava and “ t “ test which use the value of signifcant 5 % and 1 %. From the analysis of data above here the result : There is different inﬂuence that is very signifcant among treatment A, B, C, D in increasing the velocity of the 60 yard dash. Conclusion the inﬂuence of stretching-warning-up is more effective in increasing the velocity of 60 yard dash than the warming-up – stretching.